2010
DOI: 10.2174/138920010791110890
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Target Genes Across Doxorubicin Disposition Pathway: A Review

Abstract: Increased understanding of the molecular mechanisms of tumor heterogeneity combined with rapid advances in the field of pharmacogenetics and pharmacogenomics have fuelled studies on individualizing anticancer therapy. Doxorubicin (Adriamycin), is an anthracycline glycoside antibiotic originally produced by Streptomyces peucetius var. caesius, and is widely used either as a single agent or in combination with other chemotherapeutic regimens for curative, adjuvant, and palliative treatment in cancer patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 134 publications
5
93
1
8
Order By: Relevance
“…Currently, these agents are combined with conventional chemotherapeutic agent to overcome cell cycle mediated drug resistance and to enhance cytotoxic efficacy (Kelley et al, 2014). Doxorubicin modulates cell cycle through G1 and G2 phases arrest, as the result of its interaction with topoisomerase II mediated DNA damage (Lal et al, 2010). Our result confirmed that single treatment of dox 2 µM and ECS 16 µg/ml induced cell accumulation at G2/M phase.…”
Section: Discussionsupporting
confidence: 77%
“…Currently, these agents are combined with conventional chemotherapeutic agent to overcome cell cycle mediated drug resistance and to enhance cytotoxic efficacy (Kelley et al, 2014). Doxorubicin modulates cell cycle through G1 and G2 phases arrest, as the result of its interaction with topoisomerase II mediated DNA damage (Lal et al, 2010). Our result confirmed that single treatment of dox 2 µM and ECS 16 µg/ml induced cell accumulation at G2/M phase.…”
Section: Discussionsupporting
confidence: 77%
“…49 A detailed discussion of these differences are beyond the scope of this review; for additional information, see the review by Lal et al and references therein. 49 It has been hypothesized that cardiotoxicity of anthracyclines is more severe in the setting of increased ROS. Genes that regulate the NADPH oxidase complex, which is involved with ROS generation, may potentially have an effect on cardiotoxicity.…”
Section: Clinical Risk Factorsmentioning
confidence: 99%
“…Interindividual differences and interethnic variability in processing and detoxifying anthracycline may lead to differing severity of cardiotoxicity. 49 A detailed discussion of these differences are beyond the scope of this review; for additional information, see the review by Lal et al and references therein. 49 It has been hypothesized that cardiotoxicity of anthracyclines is more severe in the setting of increased ROS.…”
mentioning
confidence: 99%
“…Doxorubicin은 DNA 염기 서열 사이에 삽입되어 DNA 구조 손상을 유발하여 세포 분열을 차단시킴으로서 강력한 항암 활성을 나타내지만, 백혈 구 감소증, 빈혈, 심장 기능 상실 등의 부작용이 나타나기도 한다. Doxorubicin은 단일 항암제로도 널리 사용이 되지만, 항암활성의 상승과 부작용의 최소화를 위하여 다른 항암제와 복합 처리하여 사용되기도 한다 [10]. Doxorubicin이 암세포의 증식 억제 측면에서 세포주기 교란 [18,30] 및 세포사멸 유도 [6,28]를 포함한 전이 억제 효과 [5,14,27] 등은 이미 잘 알려진 사실이지만, 전립선 암세포에서의 전이 억제 관련 기전 연구 는 여전히 미비한 실정이다.…”
unclassified